2006
DOI: 10.1210/jc.2006-1416
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Type 2 Diabetes on Myocardial Insulin Sensitivity to Glucose Uptake and Perfusion in Patients with Coronary Artery Disease

Abstract: Myocardial IR to glucose uptake is not an inherent feature in T2DM patients with preserved LVEF. Acute physiological insulin exposure exerts no coronary vasodilation in CAD patients irrespective of T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Furthermore, in both HF and T2D, whole body metabolism is characterized by increased levels of circulating glucose, free fatty acids (FFA), and insulin [2], [3]; and the combination of HF and T2D induces complex metabolic changes in the myocardium [4]. It is a matter of debate whether these abnormalities [3], [5], [6] are causally involved in the progression of HF or merely epiphenomenal [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in both HF and T2D, whole body metabolism is characterized by increased levels of circulating glucose, free fatty acids (FFA), and insulin [2], [3]; and the combination of HF and T2D induces complex metabolic changes in the myocardium [4]. It is a matter of debate whether these abnormalities [3], [5], [6] are causally involved in the progression of HF or merely epiphenomenal [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced insulin signaling also inhibits glucose utilization by regulating the role of enzymes in the glycolysis pathway, such as hexokinase and phosphofructokinase 2 [88,89]. Declines in myocardial glucose uptake and utilization have also been observed in patients with diabetes [90].…”
Section: Insulin Resistance and Cardiac Energy Metabolismmentioning
confidence: 99%
“…They demonstrated decreased myocardial glucose utilization and reduced extraction of glucose and suggested that myocardial insulin resistance in these patients may explain their poor long-term outcome. Søndergaard et al (98) studied 27 diabetic patients with CAD and normal left ventricular function to determine whether myocardial insulin resistance was present, as it is in patients with CAD, diabetes, and abnormal left ventricular function. They were unable to demonstrate insulin resistance using PET-FDG.…”
Section: Ventricular Functionmentioning
confidence: 99%